Analysis of carfilzomib cardiovascular safety profile across relapsed and/or refractory multiple myeloma clinical trials - Chari, Ajai; Stewart, A Keith; Russell, Stuart D; Moreau, Philippe; Herrmann, Joerg; Banchs, Jose; Hajek, Roman; Groarke, John; Lyon, Alexander R; Batty, George N; Ro, Sunhee; Huang, Mei; et al. (Blood advances, 2018)
Carfilzomib is a selective proteasome inhibitor approved for the treatment of relapsed and/or refractory multiple myeloma (RRMM). It has significantly improved outcomes, including overall survival (OS), and shown superiority vs standard treatment with lenalidomide plus dexamethasone and bortezomib plus dexamethasone. The incidence rate of cardiovascular (CV) events with carfilzomib treatment has varied across trials. This analysis evaluated phase 1-3 trials with >2000 RRMM patients exposed to carfilzomib to describe the incidence of CV adverse events (AEs). In addition, the individual CV safety data of >1000 patients enrolled in the carfilzomib arm of phase 3 studies were compared with the control arms to assess the benefit-risk profile of carfilzomib. Pooling data across carfilzomib trials, the CV AEs (grade ≥3) noted included hypertension (5.9%), dyspnea (4.5%), and cardiac failure (4.4%). Although patients receiving carfilzomib had a numeric increase in the rates of any-grade and grade ≥3 cardiac failure, dyspnea, and hypertension, the frequency of discontinuation or death due to these cardiac events was low and comparable between the carfilzomib and control arms. Serial echocardiography in a blinded cardiac substudy showed no objective evidence of cardiac dysfunction in the carfilzomib and control arms. Moreover, carfilzomib had no significant effect on cardiac repolarization. Our results, including the OS benefit, showed that the benefit of carfilzomib treatment in terms of reducing progression or death outweighed the risk for developing cardiac failure or hypertension in most patients. Appropriate carfilzomib administration and risk factor management are recommended for elderly patients and patients with underlying risk factors.
Keywords: Recurrence; Male; klinické zkoušky jako téma; Risk Factors; Age Factors; Multiple Myeloma; mužské pohlaví; incidence; recidiva; Oligopeptides; kardiovaskulární nemoci; lidé; ženské pohlaví; Humans; rizikové faktory; věkové faktory; Cardiovascular Diseases; mnohočetný myelom; Female; oligopeptidy; Incidence; Clinical Trials as Topic